Response of coriander (Coriandrum sativum L.) cultivars to graded levels of vermicompost - S NARAYANA POTTY, B A VADIRAJ, SIDDAGANGAIAH SIDDAGANGAIAH (Journal of Spices and Aromatic Crops, 1998)
A field study was undertaken at Sakaleshpur (Karnataka, India) to study the response of three cultivars of corriander (Coriandrum sativum) to graded levels ofvermicompost in comparison with chemical fertilization (NPK). The study indicated that application of vermicompost significantly increased herbage and seed yield and was comparable to chemical fertilization. The herbage yield was maximum in Rcr-41 (6067.5 kg/ha) at 60th day after sowing when 15 t/ha of vermicompost was applied. Seed yield was maximum in Rcr-41 (1314 kg/ha) in plants treated with 20tlha vermicompost. The study also showed that vermicompost can be used as an alternative nutrient source for coriander cultivation.